What Sets Uveal Melanoma Apart, and How Can We Address It? A Comprehensive Review of Pathophysiology, Diagnosis and Treatment - Lissak, Karina; Szczepaniak, Zuzanna; Konopka, Agata; Wdowiak, Natalia; Choinka, Martyna; Komarów, Małgorzata; Karasińska, Dominika; Kalisiak, Jakub; Koralewicz, Mateusz; Orzeł, Milena; et al. (Quality in Sport, 2024)
Uveal melanoma (UM) is a serious condition requiring immediate medical attention. It is the most common primary intraocular cancer in adults, with an incidence of around 5.2 cases per million people annually. Nearly half of UM patients develop metastatic disease, most often affecting the liver. UM refers to any malignant tumor arising from melanocytes in the uveal tract, which includes the iris, ciliary body, and choroid. Treatment options for UM depend on several factors, including tumor size, location, and the patient’s overall health. These options may include radiation therapy, surgery, laser treatments, targeted therapies, and immunotherapy. UM is often described as an immune-privileged tumor, with a distinct immune profile compared to cutaneous melanoma (CM). This article aims to highlight the unique characteristics and challenges associated with this rare form of melanoma. By providing detailed information, the article seeks to enhance understanding and management of this rare form of melanoma.